Study of Reproductive Traits of Does in Different Altitudes of Rolpa District - Azad, MH; Dahal, M; Ali, MS (Nepalese Veterinary Journal, 2023)
Goat is a domesticated small ruminant, primarily reared by small farmers for meat production, across the country. Productivity of goat is often low, which could be related to several genetic and non-genetic factors. A field study was carried out to characterize, evaluate and estimate the effect of non-genetic factors on the reproductive performance of hill goats during December, 2015 to August 2016 in different eco-zones at Rolpa district of mid-western Nepal. Altogether 482 dams of different age groups were identified for this study. Reproductive performance were collected based on field monitoring and measurements within different altitudes of Rolpa district. Least square analysis was performed using Harvey (1990) computer software package, and means were compared using DMRT. Results revealed that the mean age of first heat in does (299 days), age at first kidding (493 days), gestation length (150 days), kidding interval (251 days), postpartum estrus (91 days), and kidding rates were (1.54 per doe), respectively. Altitude significantly influenced (P<0.001) along with parity (P<0.05) with respect to age of first heat in does. Significance difference of of kidding interval (P<0.05) was significantly influenced within different altitude of goat farming. Similarly, colour and altitude also significantly differed (P<0.05) with respect to kidding rates of does Thus the results of this study suggest that the performance of low altitude goat flocks was better than mid and high altitude goat flocks in Rolpa district in terms of production and reproduction traits. This result could be attributed to superior genotype along with better management practices followed by the farmers in Rolpa district.